Skin Patches: Organic Transdermal Iontophoresis Patch with Built‐in Biofuel Cell (Adv. Healthcare Mater. 4/2015). Issue 4 (March 2015) - Ogawa, Yudai; Kato, Koichiro; Miyake, Takeo; Nagamine, Kuniaki; Ofuji, Takuya; Yoshino, Syuhei; Nishizawa, Matsuhiko
Abstract : A transdermal iontophoresis patch driven by a built‐in biofuel cell is developed by M. Nishizawa and team on page 506 using only disposable organic materials: enzyme, conducting polymer‐based internal resistor, hydrogel sheets containing fuels (sugar) and chemical to be delivered. When mounted on the skin, the patch generates a transdermal ionic current with the osmotic flow, thereby administrating the chemical into the skin.